BIMobility Simulator as a BIM-based solution for integration of e-mobility in design process. Issue 1 (1st December 2022) - Di Blasio, I; Penna, P; Monizza, G P; Riedl, M; Matt, D T
Abstract: Electromobility is an opportunity to reduce the effects of greenhouse gas (GHG) emissions on climate change. For this reason, electromobility use is increasing and designers must consider Electric Vehicle Charging Stations (EVCS) as part of the building system. Building Information Modelling (BIM)-based technologies are potentially useful for considering sustainable aspects and systems in the building process. This paper deals with the development of a BIM-based tool that integrates electromobility into construction design. The goal is to support the integration of electromobility into the design of buildings or neighbourhoods and to guide the project towards an optimal configuration. The components of the electromobility infrastructure are included in the building model and an automated data exchange process between BIM software and Microsoft Excel evaluates some Key Performance Indicators (KPIs). The KPIs are shown by means of a user interface with a series of graphs and they allow to evaluate the most efficient scenario by comparing different project alternatives. The paper describes how the information flow has been structured, in order to automatically evaluate the electromobility integration and optimize the design process.